Pengaruh Terapi Kompres Air Hangat terhadap Nyeri Post Operasi ORIF pada Pasen Fraktur di RSUD Dr. Doris Sylvanus Palangka Raya - Vina Agustina; Suryagustina Suryagustina; Henry Wiyono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
A fracture or often called a fracture is a break in the continuity of bone tissue and is determined according to its type and extent. Pain is the most common complaint in fracture patients. Based on the results of the preliminary survey on February 14, 2018, in the Dahlia room, RSUD dr. Doris Sylvanus Palangka Raya, from 10 patients, it was found that 6 patients did not know that warm water compress therapy could reduce pain and 4 patients had heard that warm water compresses could reduce pain but still did not dare to take action alone without advice from a health professional. The results of the analysis research with the Wilcoxon test obtained a significant p-value (0.008 <0.05), then Ha is accepted, which means that there is an effect of giving warm water compress therapy before and after on the postoperative pain of ORIF in fracture patients. It can be concluded that the factors that influence the provision of warm water compress therapy to postoperative pain in ORIF fracture patients are age and gender (internal factors) and external factors including the compressing medium, warm water temperature, and the duration of the compress so that the warm water compress method is effective against decreasing intensity. pain. Health workers are advised to apply warm compress therapy as an intervention to reduce postoperative pain in patients with ORIF fractures.